Weak ferromagnetism and superparamagnetic clusters coexistence in YFe1−xCoxO3 (0 ≤ x ≤ 1) perovskites - Pomiro, F.; Gil, D.M.; Nassif, V.; Paesano, A.; Gómez, M.I.; Guimpel, J.; Sánchez, R.D.; Carbonio, R.E.; Guimpel, Julio (Elsevier, 2017)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina